(untitled) (Journal of history, 2018)
In the article, the author examines the problems of the relationship between the Kazakh Khanate and the Mawarannahr Shayban dynasty of the late 16th century. The core of this relationship was the struggle for Turkestan. In the article the author, relying on sources, examines the history of these battles, investigates the facts that Tauekel Khan in the struggle with the Shayban ruler Abdullah II Khan sent an ambassador, and also about establishing a connection between the Kazakh ambassador, the Iranian ambassadors in Moscow and the people of Abbas Shah. Even in the struggle against Mawarannahr, there is a possibility that a military alliance between the Kazakh Khanate and Iran can be established. The reasons for the effectiveness of Tauekel Khan’s campaigns are the personal qualities of the khan, the unity of the Kazakh society. Because of this campaign, the Turkestan region finally became a part of the Kazakh Khanate.